Kindness as a practice of Kittay's 'doulia' in higher education: caring for student carers during COVID-19 and beyond. (10th February 2022) - Overgaard, Charlotte; Mackaway, Jacqueline
Abstract : Recognising dependency as a fundamental aspect of existence and activating Kittay's reciprocity principle, 'doulia', we investigate the impacts of COVID-19 on student carers at an Australian university, to what extent teaching staff care for student carers and which pedagogies and teaching practices aid student carers. Analysing the experiences of social science students shortly after the lockdown in 2020, we find that pedagogies of kindness and flexibility support student carers. We call on teaching staff to recognise students' inevitable dependencies and commit to pedagogies of kindness.